Measurement properties of the construct of the code of ethics content: The South African experience - Mercy Mpinganjira; Mornay Roberts-Lombard; Goran Svensson; Greg Wood (South African Journal of Business Management, 2018)
Background: Many organisations develop codes of ethics to help guide business conduct. However, not much is known about the contents of codes of ethics. Objectives: This article aims at investigating the code of ethics content construct and its measurement properties using a sample of firms from South Africa. Method: The study followed a quantitative research approach. The sampling frame consisted of the top 500 companies in South Africa. A structured questionnaire was administered using the telephone survey method. The respondents consisted of company secretaries and heads or managers responsible for ethics in the respective companies. At the end of the data collection period, a total of 222 usable responses were obtained. Results: The findings show that South African top companies have comprehensive codes of ethics as evidenced by the high mean values obtained from all of the content items under investigation. The findings also support the notion that the code of ethics content construct is multidimensional. Seven different dimensions were confirmed in the analysis. The measurement model of the ethics content construct was found to be valid as evidenced by the goodness-of-fit measure and measures of validity. Conclusion: The study shows that the code of ethics construct is multi-dimensional in nature. The framework provided in this study can also be used in developing, evaluating and strengthening existing codes where such need arises. This study contributes to theory on business ethics and presents the first tested measurement model of the code of ethics construct in South Africa.
Keywords: 650